Environmental Pollution Select Proceedings of ICWEES-2016 (Water Science and Technology Library,, 2018)
This book comprises select proceedings of the International Conference on Water, Environment, Energy and Society. The book is divided into five parts. The first part deals with some aspects of environmental pollution such as socio-economic environment assessment for sustainable development, environmental issues due to fire in coal Mines and its impact and suggestions for implementing precautionary and control measures, redevelopment of urban slum dwellings: issues & challenges, air and noise pollution in mega cities, importance of indoor environmental quality in green buildings. Part II discusses pollution indicators such as assessment and prediction of environmental noise, fuzzy logic based performance evaluation, fish biodiversity and its periodic reduction, effects of anthropogenic activities on fresh water ecosystems, and monitoring of air pollution. Part III focuses on generation of pollution namely biomedical waste generation and management, heavy metal leaching, etc. Water quality assessment is described in Part IV. The Part V presents water quality modeling. The book will be of interest to researchers and practitioners in the field of water resources, hydrology, environmental resources, agricultural engineering, watershed management, earth sciences, as well as those engaged in natural resources planning and management. Graduate students and those wishing to conduct further research in water and environment and their development and management will also find the book to be of value.